Pengembangan Media Edukasi Animasi Interaktif sebagai Upaya Pencegahan Dini Kejadian Stunting di Kabupaten Lombok Barat - Erien Luthfia; Dewi Puspa Ariyanti; Hadi Kusuma Atmaja (Jurnal Kesehatan Manarang, 2022)
Stunting is one of the nutritional problems faced in the world. Stunting prevention intervention activities include health education through audio-visual media, but this still experiences obstacles, namely there is no special audio-visual material about stunting and its production is still limited to the campaign period only. It is predicted that there will be several alternatives for updating audio-visual materials for different target groups and that they can be broadcast consistently, so that the public understands ways to prevent stunting. The purpose of this study was to develop interactive educational media as an effort to prevent early stunting. The research design used Quasy experimental. Based on the results of the study, all respondents (100%) from the intervention group and the control group complied with the recommendations in educational media, either through interactive animations or leaflets. Analysis of the t-test value of p = 0.00 < 0.05. this shows that there is no significant difference between the intervention group and the control group. Interactive animated video and leaflets are equally effective for education to prevent stunting risk. The interactive animation educational as a result of the development of this research is effective in preventing the risk of stunting.